Success Factors Towards Implementation Of Business Continuity Management In Organizations - Noorul Halimin Mansol,; Najwa Hayaati Mohd Alwi; Waidah Ismail (Infonomics Society,UK, 2024)
International Journal of Digital Society (IJDS), Volume 5, Issue 1, March 2014